The RSNA Image Sharing Network. - Langer, S.; Tellis, W.; Carr, C.; Daly, M.; Erickson, B.; Mendelson, D.; Moore, S.; Perry, J.; Shastri, K.; Warnock, M.; Zhu, W. (Journal of Digital Imaging, 2015)
In the era of health information exchanges, there are trade-offs to consider when sharing a patient's medical record among all providers that a patient might choose. Exchange among in-network partners on the same electronic medical records (EMR) and other integrated information systems is trivial. The patient identifier is common, as are the relevant departmental systems, to all providers. Difficulties arise when patient records including images (and reports) must be shared among different networks and even with the patients themselves. The National Institutes of Health (NIH) challenged Radiological Society of North America (RSNA) to develop a transport method that could supersede the need for physical media (for patients or other providers), replace point-to-point private networks among providers, and enable image exchange on an ad hoc basis between arbitrary health networks without long legal delays. In concert with the evolving US health care paradigm, patient engagement was to be fundamental. With Integrating Healthcare Enterprise's (IHE's) help, the challenge has been met with an operational system.